A Comparative Exposition of the Law of Husband and Wife in terms of Islamic Law, South African Law and the Law of England and Wales - Part 1 - Razaana Denson, (Obiter, 2021)
The primary concern of this article is a comparative analysis of marriage law in three legal systems – namely, Islamic law, South African law and English law. The similarities and differences between these legal systems are highlighted. The comparative analysis demonstrates that although there are similarities in the three legal systems, the differences outweigh the similarities. This begs the question whether Islamic law (Muslim personal law in general and family law in particular) can be recognised and accommodated and implemented in the South African and English legal systems (both constitutional democracies) without compromising the principles of Islamic law, while at the same time upholding the rights contained in the Bill of Rights. To this end, a comparative analysis is undertaken of the law of marriage that entails a discussion, inter alia, of betrothal (engagement), the legal requirements for a marriage, as well as the personal and proprietary consequences of a marriage as applicable in Islamic law, South African law and English law.